The Routledge companion to Jewish history and historiography
1 online resource.
Keywords: The Routledge Companion to Jewish History and Historiography provides an overview of Jewish history from the biblical to the contemporary period, while simultaneously placing Jewish history into conversation with the most central historiographical methods and issues and some of the core source materials used by scholars within the field. The field of Jewish history is profitably interdisciplinary. Drawing from the historical methods and themes employed in the study of various periods and geographical regions as well as from academic fields outside of history, it utilizes a broad range of source materials produced by Jews and non-Jews. It grapples with many issues that were core to Jewish life, culture, community, and identity in the past, while reflecting and addressing contemporary concerns and perspectives. Divided into four parts, this volume examines how Jewish history has engaged with and developed more general historiographical methods and considerations. Part I provides a general overview of Jewish history, while Parts II and III respectively address the rich sources and methodologies used to study Jewish history. Concluding in Part IV with a timeline, glossary, and index to help frame and connect the history, sources, and methodologies presented throughout, The Routledge Companion to Jewish History and Historiography is the perfect volume for anyone interested in Jewish history.